2002
DOI: 10.1046/j.1365-2249.2002.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in rheumatoid fibroblast-like synovial cells through activation of peroxisome proliferator-activated receptor γ-mediated signalling pathway

Abstract: SUMMARY Peroxisome proliferator‐activated receptor γ (PPARγ) is a ligand dependent transcriptional factor known to be a regulator of adipogenesis. Recent studies have also shown that stimulation of PPARγ inhibits the transcriptional activities of other nuclear factors and down‐regulates proinflammatory cytokine synthesis in T cells and monocytes. We examined, in the present study, the functional significance of PPARγ expressed in fibroblast‐like synovial cells (FLS) isolated from patients with rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
1
27
0
4
Order By: Relevance
“…[3][4][5][6] Usually, synovial fibroblast adipogenesis was induced using a mixture of substances, including methyl-isobutylxanthine and indomethacine 5 or insulin, dexamethasone and troglitazone. 4,6 These adipocyte-like cultures 4,6 expressed to a lesser degree the proinflammatory cytokines, IL-6 and IL-8, and the adipogenesis of synovial fibroblasts has been proposed as an anti-inflammatory tool for combating rheumatoid diseases. 6 However, the same work showed that TNF-a inhibited synovial fibroblast adipogenesis, Genistein induces adipogenesis but not leptin B Relic et al suggesting limiting effects of adipogenic substances in inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Usually, synovial fibroblast adipogenesis was induced using a mixture of substances, including methyl-isobutylxanthine and indomethacine 5 or insulin, dexamethasone and troglitazone. 4,6 These adipocyte-like cultures 4,6 expressed to a lesser degree the proinflammatory cytokines, IL-6 and IL-8, and the adipogenesis of synovial fibroblasts has been proposed as an anti-inflammatory tool for combating rheumatoid diseases. 6 However, the same work showed that TNF-a inhibited synovial fibroblast adipogenesis, Genistein induces adipogenesis but not leptin B Relic et al suggesting limiting effects of adipogenic substances in inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, synovial fibroblasts were recognized as multipotent cells that can differentiate into osteocytes, chondrocytes and adipocytes. [3][4][5][6] In addition, synovial fibroblasts were shown to express specific markers of bone marrow-derived multipotent stem cells (MSCs), such as CD-105, CD-90 and CD-73. 3,7 Among the different sources of MSCs, such as bone marrow, skeletal muscle and adipose tissue, synovium was recognized as a potent source.…”
mentioning
confidence: 99%
“…In the present work Rtz was shown to inhibit IL-1␤-induced MMP9 gelatinolytic activities and MMP3 and MMP13 mRNA levels. PPAR␥ agonists were also found to inhibit MMP3 expression in human rheumatoid fibroblast-like synoviocytes (44). Down-regulation of MMP9 by natural (15d-PGJ2) and synthetic (GW7845) PPAR-␥ ligands in PMA-stimulated THP-1 monocytes has been consistently observed (31).…”
Section: The Ppre Sequence Situated At ϫ83 To ϫ71 In the Mmp1 Promotementioning
confidence: 94%
“…We previously reported apoptosis (Kawakami et al 1999Miyashita et al 2003Miyashita et al , 2004Tamai et al 2006), cell differentiation ), cell proliferation (Eguchi et al 1992;Migita et al 2000Migita et al , 2001, signal transduction (Yamasaki et al , 2002, sensitivity to drugs , and protein expression of the rheumatoid synovial cells Tanaka et al 2004) using the long-time cultured synovial cells derived from the knee joint replacement surgery. As the cell population and the expression of TNF receptors both dramatically changed in the synovial cells derived from both surgery and a synovectomy after long-term cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Informed consent was obtained from all participating subjects, and the study was conducted in accordance with the human experimental guidelines of our institution. Synovial cells were isolated from the synovial tissues by an enzymatic digestion, as described previously (Yamasaki et al 2002). Adherent synovial cells of at least four passages were used in this experiment as the cultured synovial cells.…”
Section: Cellsmentioning
confidence: 99%